Confirmation: What's in the evidence? - Mitesh Kataria (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
In this paper, I discuss the difference between accommodated evidence (i.e. when evidence is known first and a hypothesis is the proposed to explain and fit the observations) and predicted evidence (i.e., when evidence verifies the prediction of a hypothesis formulated before observing the evidence) from a behavioral as well as a statistical perspective. Using a factorial survey on a sample of students, I show that predicted evidence is perceived to constitute stronger confirmation than accommodated evidence. This position deviates from the standard Bayesian epistemological theory of confirmation where accommodated and predicted evidence constitute equally strong confirmation. The findings suggests that trusting a model to predict correctly is intrinsically related to trust in the proposers (i.e., the scientists') level of knowledge, and relatively more subjects are persuaded by a proposers abilities if the proposer is successful in predicting rather than accommodating evidence. The existence of an indirect relationship between hypothesis and evidence can be considered to impose undesirable subjectivity and arbitrariness on questions of evidential support.
Keywords: C11; C12; C80; 330; evidence; methodology; prediction